EFEKTIVITAS REHABILITASI TERHADAP PELAKU PENYALAHGUNAAN NARKOBA (STUDI DI BADAN NARKOTIKA NASIONAL KOTA CIREBON) - Virgiawan Listianto (Jurnal Idea Hukum, 2020)
Drug use is a crime that has brought about victims of drug use in the community.Ideally, narcotics are required in the world of health and science, but in the same time the use of illegal narcotics is a very dangerous one, so that legal devices aimed at controlling the distribution and use of such addictive substances are indispensable. The method of approach used in this research is a qualitative method with a sociological juridical approach (Sosio-legal research). The specification of this research is descriptive according to the problems and objectives in this research. Primary data sources and secondary data sources and are analyzed in a qualitative method. The efforts to implement rehabilitation conducted by the Government against narcotics users pursuant to article 54 Juncto Article 55 Act number 35 year 2009 about narcotics is doing various measures to prevent narcotic abuse, by means of rehabilitation can help the victims, rehabilitation there are two: medical rehabilitation and social rehabilitation, and counseling.